EFEKTIFITAS PEMBELAJARAN ONLINE DAN OFFLINE (HYBRID LEARNING) BAGI SISWA DI SMA NEGERI 1 TONDANO - Mesra, Romi; Mononege, Nonsi; Korah, Yossi Christian (Lembaga Penelitian dan Pendidikan Mandala, 2022)
Hybrid learning is also applied at SMA Negeri 1 Tondano, where initially the teaching and learning process at this school was carried out online from the homes of both teachers and students. infrastructure constraints, facilities and infrastructure are mainly related to media and learning tools that must be provided by students, but due to the different abilities of students, especially economically, there are students who can access learning smoothly and some are limping along with learning. The purpose of this study is to reveal the effectiveness of Online and Offline Learning (Hybrid Learning) for Students at SMA Negeri 1 Tondano. The method used is a qualitative research method. The results of this study are; some students have difficulty completing online learning tools, students' ability to use digital media increases, face-to-face learning becomes a variation of online learning, lecture methods are less effective in learning using online media, assignment methods or projects through digital media are of interest to students, affective assessment of students is a little difficult conducted.